2017
DOI: 10.1088/1612-202x/aa61bd
|View full text |Cite
|
Sign up to set email alerts
|

Boron-doped nanodiamonds as possible agents for local hyperthermia

Abstract: In this work, the effective heating of surrounding water by heavily-boron-doped nanodiamonds (NDs) under laser irradiation of visible wavelength was found. Using Raman scattering spectroscopy of aqueous suspensions of boron-doped NDs, it was found that this abnormally high heating results in the weakening of hydrogen bonds much more so (2-5 times stronger) than for undoped NDs. The property of boron-doped NDs to heat a solvent under the influence of laser radiation (1-5 W cm −2 ) opens broad prospects for thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…The surface of all BDNDs was cleaned by boiling nanoparticles in a mixture of sulfuric and nitric acids in the ratio 3:1 at a temperature of 200 °C for 17 h. The result of this kind of cleaning is a surface coated with −COOH groups. 11 Furthermore, the samples were purified from acids during 3−4 cycles of washing with water and subsequent centrifugation at 27 530 g for 30 min (Sigma 3-18KS centrifuge). Purification from acids ended when the BDND was stopped to precipitate.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The surface of all BDNDs was cleaned by boiling nanoparticles in a mixture of sulfuric and nitric acids in the ratio 3:1 at a temperature of 200 °C for 17 h. The result of this kind of cleaning is a surface coated with −COOH groups. 11 Furthermore, the samples were purified from acids during 3−4 cycles of washing with water and subsequent centrifugation at 27 530 g for 30 min (Sigma 3-18KS centrifuge). Purification from acids ended when the BDND was stopped to precipitate.…”
Section: Methodsmentioning
confidence: 99%
“…9,10 In the result of the study of aqueous suspensions of these BDNDs, it was found that doping of nanodiamonds with boron gives them the ability to substantially heat their environment under the laser irradiation. 11 This opens up the possibility of using BDNDs as hyperthermia agents.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This method can be applied to bulk diamond, diamond with tailored dopant properties, or isotopically purified diamond to produce NDs with the same dimensional properties 41,42 . Doped NDs are attractive materials for the study of medical oncology 43 , electrochemistry 44,45 , diamond electronics 46 , and superconductivity 47,48 . Diamond enriched with 12 C can enable increased coherence times of hosted spin systems due to the limited number of interfering spin impurities in the host material 42 .…”
Section: Discussionmentioning
confidence: 99%